1994
DOI: 10.1152/jappl.1994.76.4.1630
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E effects on indexes of lipid peroxidation in muscle from DHEA-treated and exercised rats

Abstract: Sixty-four male Sprague-Dawley rats were randomly assigned to one of eight treatment groups to determine the effects of vitamin E (VitE), dehydroepiandrosterone (DHEA), and exercise on antioxidant status in plasma and skeletal muscle. Indexes of oxidative stress were determined by measuring two markers of lipid peroxidation and the activity of two free radical scavenging enzymes. One-half of the rats had their diets supplemented with 250 IU VitE/kg of diet. One-half of the rats were injected with 0.35 mol/kg b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
4

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 0 publications
1
25
0
4
Order By: Relevance
“…However, no study has demonstrated improvement in performance after supplementation in non-deficient individuals (34)(35) . Due to α-tocoferol efficiency in reacting with peroxyl radicals, many studies have been conducted with the purpose to evaluate the effect of α-tocoferol supplementation in the LP, caused by oxidative stress induced by physical exercise.…”
Section: Vitamin Ementioning
confidence: 99%
See 1 more Smart Citation
“…However, no study has demonstrated improvement in performance after supplementation in non-deficient individuals (34)(35) . Due to α-tocoferol efficiency in reacting with peroxyl radicals, many studies have been conducted with the purpose to evaluate the effect of α-tocoferol supplementation in the LP, caused by oxidative stress induced by physical exercise.…”
Section: Vitamin Ementioning
confidence: 99%
“…Due to α-tocoferol efficiency in reacting with peroxyl radicals, many studies have been conducted with the purpose to evaluate the effect of α-tocoferol supplementation in the LP, caused by oxidative stress induced by physical exercise. Goldfarb et al (35) have observed smaller concentrations of lipidic hydroperoxides and thiobarbituric acid reactive substances (TBARS) in the plasma and in muscular fibers of rats submitted to intense exercise and supplemented for five weeks with α-tocoferol (250 UI α-tocoferol/kg of diet). Metin et al (36) also verified reduction in the TBARS concentration in rats supplemented with α-tocoferol (30 mg/kg/day) and training in swimming.…”
Section: Vitamin Ementioning
confidence: 99%
“…MDA'nın egzersizin şiddet ve süresiyle orantılı olarak oksidatif strese neden olduğu ve lipid peroksidasyon reaksiyonlarını arttırdığı düşünülmektedir (31,32). Oksijen kulanımının düşük olduğu durumlarda süperoksit radikali ve onun türevleri antioksidan savunma ile zararsızlaştırılır.…”
Section: Tartişma Ve Sonuçunclassified
“…Kanter et al (28) show that daily supplementation with a vitamin mixture containing 600 mg oL-tocopherol for 6 weeks significantly decreased levels of serum MDA and expired pentane, both at rest and after 30 min of treadmill exercise at 60 and 90% VO2max. Goldfarb et al (62) report that rats supplemented with a 250 IU vitamin E/kg diet for 5 weeks have lower TBARS and lipid peroxide levels in plasma and leg muscles after one hour treadmill exercise compared to controls. Sumida et al (63) also demonstrate a protective effect with vitamin E supplementation (300 mg/day) in reducing serum MDA concentration and enzyme markers of tissue damage during exercise.…”
Section: Non-enzymatic Antioxidantsmentioning
confidence: 99%